Voices of an Invented Landscape: Oral Memory of Colonization Villages (Anclajes, 2026)
Based on statements made by recent bibliographic sources regarding Franco'scolonization policies, the testimony of settlers in newly established towns is analyzedwith the aim of not only bringing to light ambiguities, gray areas, and contradictions—the multifaceted nature, tosay the least, of the oral memory of the colonized peoples—but also finally place protagonists ‘voices of the process at the forefront. The perspectiveadopted for the study of the testimonies is dialogic, as these are permanently placed inrelation with the assertions of the academic bibliography, with which not oalways theyagree. This variability would corroborate, once again, the complexity of rural memoryduring the Franco dictatorship.
Keywords: Colonization Villages; Francoism; Memory; Instituto Nacional de Colonización; Testimony